2019
DOI: 10.1101/722124
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Three-fluorophore FRET enables the analysis of ternary protein association in living plant cells

Abstract: Integration of signalling on the cellular level is essential for the survival of organisms.Protein-protein interaction studies provide valuable insights in these signalling events.One of the best understood signalling pathways in plants is the brassinosteroid (BR) hormone signalling pathway, which is mediated by the receptor BRASSINOSTEROID INSENSITIVE 1 (BRI1) with its co-receptor BRI1-ASSOCIATED KINASE (BAK1). Both BRI1 and BAK1 have been shown to interact with RECEPTOR LIKE PROTEIN 44 (RLP44), which was imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 99 publications
(134 reference statements)
0
10
0
Order By: Relevance
“…For example, the BRI1-dependent regulation of the vascular cell fate in the MZ of the root or the BRI1-mediated cross-tissue control of the cell wall homeostasis require nano-organized BRI1 complexes that contain at least additionally RLP44 ( Wolf et al, 2014 ; Holzwart et al, 2018 ). Moreover, RLP44-containing BRI1/BAK1 nanoclusters are spatially distinct from for instance FLS2/BAK1 nanoclusters ( Glöckner et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the BRI1-dependent regulation of the vascular cell fate in the MZ of the root or the BRI1-mediated cross-tissue control of the cell wall homeostasis require nano-organized BRI1 complexes that contain at least additionally RLP44 ( Wolf et al, 2014 ; Holzwart et al, 2018 ). Moreover, RLP44-containing BRI1/BAK1 nanoclusters are spatially distinct from for instance FLS2/BAK1 nanoclusters ( Glöckner et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Trifluorophore FRET-FLIM and trimolecular fluorescence complementation (Glöckner et al, 2019;Offenborn et al, 2015) have been shown to work in plants. The spatial tagging limitations required to have a positive readout using the above tools however are likely limiting to apply this for any random complex of choice.…”
Section: Ksp Is a Valuable Tool To Visualize Ppimentioning
confidence: 99%
“…Recently FRET-FLIM has been developed into a three-fluorophore system which enabled to visualize triple PPIs (Glöckner et al, 2019). Nevertheless, FRET-FLIM is quite-labor intense, requires careful interpretation and multiple control assays.…”
Section: Introductionmentioning
confidence: 99%
“…However, the cell wall also feeds back on BR signalling [153]. The state of pectin, an important component of the plant cell wall and a dynamic regulator of its properties [154][155][156][157], is relayed to the BR receptor complex by RECEPTOR-LIKE PROTEIN44 (RLP44), which directly interacts with both BRI1 and BAK1, likely acting as a scaffold to promote their association [103,158,159]. In line with this notion, RLP44 is sufficient to promote BR signalling, at least partially independent of BRs [103].…”
Section: New Inputs and Outputs For Bri1 Signallingmentioning
confidence: 99%